Enteric methane emissions mitigation in U.S. beef production: industry adoption, public perception, and potential market impacts - Luke, Jaime Rebecca (My University, 2024)
Chapter 1 Cattle are ruminant livestock that emit enteric methane (CH₄) as part of their natural digestive process. The U.S. beef cattle industry is receiving pressure to reduce greenhouse gases emissions, including methane. The U.S. Roundtable for Sustainable Beef has set a target for the U.S. feedlot sector to reduce emissions by 10% per pound of beef by 2030. Feed additive 3-Nitrooxypropanol (3-NOP) has been developed to help mitigate methane emissions. While not yet approved for use in U.S. beef production, adoption of 3-NOP in U.S. feedlots upon approval remains unknown as no widespread economic incentive currently exists in the marketplace to spur adoption. The objectives of this study are: (1) to determine potential 3-NOP adoption by U.S. feedlot cattle producers given various marketplace incentives and (2) to explore how differing approaches to reducing emissions from beef production to achieve sector targets impact social welfare. Our study uses data from a U.S. feedlot producer survey to estimate willingness-to-adopt (WTA) measures. Regression results are used to map potential adoption of 3-NOP given various market and policy scenarios. The survey sample is then split into small producers (<2000 head sold in last 12 months) and large producers (2000+ head sold in last 12 months) to determine differences in WTA based on operation size. We find that producers prefer incentives in the form of processor premiums over government subsidies. The incentive level needed to spur adoption increases as the implementation cost of 3-NOP increases and decreases if net profit estimations are included in the messaging. On average, small producers require a higher incentive to adopt 3-NOP than large producers. Improving the emissions reduction efficacy of 3-NOP reduces the level of incentive needed to achieve aggregate emissions targets. The least expensive avenue to achieve emissions reduction targets results in greater outlays to large producers as compared to small producers. The marginal cost to society of feeding 3-NOP to an additional steer or heifer in the feedlot increases with each animal. As such, it may be that improving the efficacy of 3-NOP through increased investment in research and development is less costly than spurring more producers to adopt the additive in their feed rations. Ultimately, producers, processors, beef consumers, voting residents, taxpayers, and policymakers all have influence in shaping how the beef industry tackles the emissions reduction conundrum. Chapter 2 U.S. beef cattle producers have been receiving pressure to reduce methane emissions from beef production as climate change concerns mount. Demand for “climate-friendly” beef could create economic incentives that spur U.S. cattle producers to adopt emissions reducing practices. Beef products with varying climate claims have recently been introduced in the retail sector, stemming from various countries-of-origin. This study quantifies differences in U.S. consumer willingness-to-pay (WTP) for distinct climate claims on ground beef and ribeye steak products, accounting for country-of-origin (COO) impacts. Using data from a nationally representative survey of the U.S. public, no statistical difference in WTP estimates is found among climate claims within beef product categories. This suggests U.S. consumers are, on average, indifferent among the climate claims on beef products included in this study. U.S. consumers are willing to pay a higher price premium for climate claims on ribeye steak (up to 5.3%) as compared to ground beef (up to 2.8%), and they prefer U.S. beef products as compared to those from Australia, Canada, and Uruguay. Imported beef products with climate claims are unlikely to have major implications on the demand for U.S.-produced beef. Ultimately, beef producers should consider the cost of implementing climate-focused production practices to determine if garnering market premiums for climate claims on beef products would be a profitable endeavor. Chapter 3 Many countries have begun introducing policies aiming to reduce emissions from beef production. Several strategies are being researched and developed to reduce such emissions. This study explores U.S. public sentiment toward various beef production emissions-reduction strategies and quantifies support for potential policy measures. Using data from a nationally representative survey, it is found that feeding seaweed to cattle is the most preferred strategy followed by letting either the beef industry or the U.S. Department of Agriculture decide how to reduce emissions from beef production. The U.S. public shows greater support for subsidies versus mandates if they recognize that mandates could increase the price of beef. The strategy with the highest estimated subsidy support, as funded by the U.S. public, is seaweed. However, these subsidy levels are less than the projected cost of the product in practice, so producer adoption of seaweed as triggered by a U.S. public-supported subsidy is unlikely. A more plausible solution to subsidizing a subset of beef producers to reduce emissions may be connecting climate-concerned residents who are willing to fund a subsidy to producers who are willing to adopt climate-focused practices.
Keywords: Beef production; Climate mitigation; Enteric methane emissions; Policy; Survey; Willingness-to-pay